Digestibilidad de una mezcla de kudzu (Pueraria phaseoloides) y pasto Honduras (Ixophorus unisetus (Presl) Schlecht) - Bateman, J.V.; Peralta, M. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Four purebred Brown Swiss heifers averaging 453 Kg. in weight were fed a mixture consisting of approximately 40% Tropical Kudzu (Pueraria phaseoloides) and 60% Honduras grass (Ixophorus unisetus (Presl) Schlecht). Consumption was high enough to exceed norms established by the National Research Council for digestible protein. However, only about 93% of the energy needs were filled. The mixture contained 45.1 Kg. T.D.N. per 100 Kg. of Dry Matter and each Kg. of Dry Matter contains 1950.841 KCal of digestible energy.